Aspectos de Alfabetização Científica nos livros didáticos de Ciências dos anos finais do Ensino Fundamental - Oldoni, Josiani Fátima Weimer Baierle (2019)
This research aimed to investigate whether the textbooks approved by the guide of the Programa Nacional de Avaliação do Livro Didático - National Program of Evaluation of the Textbook - (2017) present means that allow the scientific literacy of the students. For the development of the study, the analysis of 11 textbooks of the 6th year of Elementary School II was carried out. The research is qualitative. The data were analyzed through the Discursive Textual Analysis - DTA – by the authors Roque Moraes and Maria do Carmo Galiazzi, in a work dating from 2007. The dimensions of scientific literacy developed by Rosana Franzen Leite in 2015, as well as its structuring axes of the authors Lúcia Helena Sasseron and Ana Maria Pessoa de Carvalho, from 2008, formed the basis of the theoretical reference. Based on this foundation, the research proposed dimensions on scientific literacy for the analysis of textbooks, such as a) aspects of the nature of science, b) relationship between scientific and everyday knowledge and c) socio-scientific aspects. From the analysis of the textbooks, it was identified that the approaches on the content of the dimensions are found during the texts of the chapters or in extra sections, boxes, and text boxes. In the dimension of aspects of the nature of science, discussions have emerged on scientific knowledge and representations of science, male representation, and absence of women and the work of the scientist. In the dimension of the relationship between scientific and everyday knowledge, the discussions were about contextualization as exemplification or information or even understanding of daily life and contextualization as a critical understanding of relevant scientific and technological issues that affect society. In terms socio-scientific aspects, whether the approaches were thematic or specific and the objectives were under analysis: i) relevance, ii) motivation, iii) communication and argument, iv) analysis and v) understanding. In the end, the elaboration of a parameter was possible, evidencing which textbooks presented the highest number of scientific literacy indicators